Effective methylation triage of HPV positive women with abnormal cytology in a middle-income country (2020)
ABSTRACT : The S5-methylation test, an alternative to cytology and HPV16/18 genotyping to triage high-risk HPV-positive (hrHPV+) women, has not been widely validated in lowmiddle-income countries (LMICs). We compared S5 to HPV16/18 and cytology to detect cervical intraepithelial neoplasia Grade 2 or worse (CIN2+) and CIN3+ in hrHPV + women selected from a randomized pragmatic trial of 2661 Colombian women with an earlier-borderline abnormal cytology. We included all hrHPV+ CIN2 and CIN3+ cases (n = 183) age matched to 183 <CIN2 hrHPV+. Baseline specimens were HPVgenotyped and tested by S5-methylation, blinded to cytology, histology and initial HPV results. We evaluated the test performance of predefined S5-classifier (cut-point 0.8) and a post hoc classifier at a different cut-point (3.1). S5 sensitivity for CIN2+ was 82% (95% confidence interval [CI] 76.4-87.5) and for CIN3+ 77.08% (95% CI 65.19-88.97). S5 sensitivity was higher than HPV16/18 sensitivity (48.1%, 95% CI 40.85-55.33) or cytology (31.21%, 95% CI 24.50-37.93) but with lower specificity (35%, 95% CI 28.1-42). At cut-point 3.1, S5 sensitivity for CIN2+ (55.2%, 95% CI 48-62.4) or CIN3+ (64.6%, 95% CI 51.0-78.1) was also superior to HPV16/18 (P < .05) or cytology (P < .0001). At this cut-point S5 specificity (76%, 95% CI 69.8-82.1 for <CIN2) was higher than HPV16/18 (67.21%, 95% CI 60.41-74.01, P = .0062) and similar to cytology (75.57%, 95% CI 69.34-81.79, P = 1). HPV16/18 plus cytology sensitivity was similar to S5 for CIN3+, however, false-positive rate was higher (50.27% vs.24.04%). High sensitivity is crucial in LMICs, S5-methylation exceeded HPV16/18 or cytology sensitivity with comparable specificity for CIN2+ and CIN3+ in hrHPV positive Colombian women. Furthermore, S5 triage had comparable sensitivity and significantly fewer false positives than cytology and HPV16/18 combination.